Memperkuat Daya Tahan Organisasi: Mengintegrasikan Identifikasi, Evaluasi, dan Pengendalian Risiko - akbar, yodi alrizky (Maliki Interdisciplinary Journal, 2024)
In this article, we will discuss risk management strategies that can be used to deal with potential risks that an organization may face. In general, it is discussed about the importance of managing risk well through risk identification, risk evaluation, determining risk tolerance, and establishing an internal control system. This article also discusses risk management policies, such as determining risks related to products and transactions, determining measurement methods, setting risk limits, determining risk ratings, preparing emergency plans, and establishing internal controls. To achieve their goals, an organization must have a sound and comprehensive risk management policy that will enable it to manage risks appropriately according to tolerable risk levels.